Exploring Student Representative Council’s Experiences at Historically White Universities: A Meta-Narrative Review (Journal of Student Affairs in Africa, 2024)
Student representation has been conceptualised and studied in different ways and by different researchers for more than 10 years. Despite the vast studying of student representation, the number of meta-narrative reviews are scattered in literature and are insufficient to show the summarised or over-arching developments that have taken place in student representative councils (SRC). This article focuses on providing a summary of the occurrences that affected student representatives in historically white universities (HWU) from 2011 to 2022. To provide a map, a focused literature search that describes and compares the different conceptualisations and studies of student representation experiences at HWU and to make sense of the research area, a meta-narrative review was conducted. The resources for the review were found through scoping and systematic searches of electronic searches, journal articles and book chapters. The major themes found through synthesis and analysis included experiences of diversity, experiences of disruption, the use of protests and the development of policy promoting transformation in HWU. The review concludes by highlighting the significance of understanding the experience of student representatives by pursuing a scholarship of integration that consolidates university governance efforts that strongly impact holistic student success.
Keywords: student representative councils; historically white universities; disruption; diversity; meta-narrative review